Atividade fotossintética em plantas do gênero Prunus - Martinazzo, Emanuela Garbin (2011)
The growth and development of plants of the rosaceae family present variations of physiological processes during the annual cycle. Plant species that occur over a heterogeneous environment are subject to conditions of multiple stresses due to the variety of weather conditions. In this context, water stress, flooding or deficit, has a profound impact on ecological and agricultural systems. The kinetics of chlorophyll a fluorescence is a quite sensitive to environmental stress, and small changes in structure and operation, can be easily detected by their analysis. This work was divided into three experiments, with the aim of evaluating the variation of the kinetics of chlorophyll fluorescence in the plants of the genus Prunus. The first was conducted in the field, the Centro Agropecuário da Palma, with six treatments (rootstocks) associated with Maciel. They were accompanied by a period of approximately 150 days the length of the leaf chlorophyll content and chlorophyll a fluorescence kinetics. The second and third experiments were conducted in a greenhouse to cultivate plum America (P. salicina) cultivar and hybrid-cup "GxN-9" (P.dulcis Mill. X P.persica L. Batsch) respectively. In both experiments, plants were kept for 11days under water restriction and 10 days of flooding, with three treatments (control, drought and flooding). Analysis of gas exchange and chlorophyll a fluorescence were monitored regularly every three days. During the experiment a variation of fluorescence parameters are affected by ontogeny of the leaves and especially the high rainfall recorded at 97 days of the beginning of the experiment. By analyzing of JIP-Test, damage to the photosynthetic system were checked, along with the best association with Maciel x rootstock Rubirá. In experiment 2, plum plants subjected to water stress, showed a reduction in photosynthesis due to reduced stomatal conductance and the increase in the flow dissipation by reaction center (DI/RC) most striking under conditions of water deficit. In the third experiment, the lowest photosynthetic activity of the hybrid "GxN-9" is related to the decrease in carboxylation efficiency, while the quantum yield of electron transport was more affected by flooding. Thus, the results suggest that plants plum America is growing more sensitive to water deficit conditions, and the rootstock hybrid "GxN-9", the conditions of soil flooding.